IMF Policies and Practices on Capacity Development. (Policy Papers; Policy Paper, 2014)
This statement summarizes the IMF's policies and practices with regard to the delivery of capacity development (CD) activities. It updates the 2001 Policy Statement on IMF Technical Assistance, incorporating the principles outlined in the 2013 CD strategy paper approved by the Executive Board as well as relevant principles described in earlier documents considered by the Executive Board.1 The purpose of the statement is to consolidate the guiding principles endorsed by the Board with policies and practices that are within the authority of IMF's Management and are followed by staff in carrying out capacity development activities. The statement is expected to be of use to IMF staff, Executive Directors and their staff, country authorities, and donors. It also serves as a point of reference for future reviews of the IMF's CD activities.